2018
DOI: 10.1007/s00334-018-0703-x
|View full text |Cite
|
Sign up to set email alerts
|

Ceremonial plant consumption at Middle Bronze Age Büklükale, Kırıkkale Province, central Turkey

Abstract: A shaft-like room at the Middle Bronze Age site of Büklükale in central Turkey preserved a rich archaeobotanical assemblage of charred and mineralised plant remains, dominated by fruits, spices and nuts mixed with probable bread and wood charcoals. The remains were recovered in association with numerous ceramic vessels, jewellery, and exotic artefacts. We combine identification and analysis of the seeds and wood charcoals contained in this deposit with studies of Old Assyrian and Hittite textual records to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Archaeobotanical studies of grain tissues have already successfully contributed to the knowledge of the ingredients and processes involved in the production of cereal-based foodstuffs, not only of entire "loaves" [58,66,122] but also of small fragments [75,79,80,82,123,124]. These studies have demonstrated that patches of aleurone tissue are not only still recognizable in charred fragments of ground food preservations from archaeological contexts (Fig 4), but the aleurone tissue's structure [86,87] has also successfully been used for the differentiation of barley (Hordeum vulgare) from other Old World cereals and grasses [58,66,80,82,122,125,126].…”
Section: Research Goalsmentioning
confidence: 99%
“…Archaeobotanical studies of grain tissues have already successfully contributed to the knowledge of the ingredients and processes involved in the production of cereal-based foodstuffs, not only of entire "loaves" [58,66,122] but also of small fragments [75,79,80,82,123,124]. These studies have demonstrated that patches of aleurone tissue are not only still recognizable in charred fragments of ground food preservations from archaeological contexts (Fig 4), but the aleurone tissue's structure [86,87] has also successfully been used for the differentiation of barley (Hordeum vulgare) from other Old World cereals and grasses [58,66,80,82,122,125,126].…”
Section: Research Goalsmentioning
confidence: 99%
“…Sometimes, even the expected main ingredients (e. g. flour) in a sample do not deliver enough identifiable material, while possible accessory components—accidental ones such as glumes, or intentional ones such as condiments—are even more difficult to track. However, there are cases where even condiments have successfully been identified [ 82 , 143 , 144 ].…”
Section: Methodsmentioning
confidence: 99%
“…This special issue includes three articles that adopt Naomi's diverse toolkit to explore plant use in the past, drawing on Roman murals (Gleason 2019), Hittite and Old Assyrian texts (Fairbairn et al 2019), and early 20th century cookbooks (Popper 2019). Gleason (2019), who previously coedited the volume The Archaeology of Garden and Field with Naomi (Miller and Gleason 1994a), considers what we can learn about Roman gardening practices by examining archaeobotanical evidence from the gardens of Pompeii and Herculaneum alongside Roman murals from those and other neighbouring sites.…”
Section: Analysing Textual and Iconographic Recordsmentioning
confidence: 99%
“…She finds that each line of evidence gives a distinct set of insights into Roman garden design and maintenance practices, and that together they produce new understandings of both Roman landscape aesthetics and pruning technologies. Fairbairn et al (2019) consider the unique composition of the archaeobotanical assemblage from the fill of a single shaft-like room at the Middle Bronze Age site of Büklükale, Turkey, which they interpret in light of Old Assyrian and Hittite texts as a ritual deposit. Along with imported artefacts, the inclusion of rare and exotic plant types, especially fruits and spices, in both the seed and wood assemblages, as well as the inclusion of seeds from species with well-known medicinal uses, found in this context alongside imported artefacts, offers a new perspective on ritual feasting practices during the Bronze Age.…”
Section: Analysing Textual and Iconographic Recordsmentioning
confidence: 99%